2020
DOI: 10.5860/crl.81.5.808
|View full text |Cite
|
Sign up to set email alerts
|

Beyond the Surveys: Qualitative Analysis from the Academic Reading Format International Study (ARFIS)

Abstract: The Academic Reading Format International Study (ARFIS) collected data from more than 21,000 university students in 33 countries regarding their reading format (print or electronic) preferences and behaviors when engaging with academic texts during a three-year period. Quantitative analysis shows a consistent preference for print reading among most students worldwide. This paper presents new findings from our qualitative analysis of students' survey comments, addressing the questions: Why do students prefer to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 9 publications
1
10
0
1
Order By: Relevance
“…In the Reader Objectives factor, we include the learning goal dimension, reflecting that the learning goals of the reader are associated with their stated format preferences, as well as the task importance dimension, which recognizes that higher-stakes and more effortful reading tasks are associated with greater print preference. This reflects data such as the expressed willingness of print-preferring tertiary learners to read electronically in cases where texts were “short…[and] of less importance, relevance, and difficulty” (Mizrachi and Salaz, 2020, p. 817).…”
Section: Ream Modelmentioning
confidence: 98%
See 2 more Smart Citations
“…In the Reader Objectives factor, we include the learning goal dimension, reflecting that the learning goals of the reader are associated with their stated format preferences, as well as the task importance dimension, which recognizes that higher-stakes and more effortful reading tasks are associated with greater print preference. This reflects data such as the expressed willingness of print-preferring tertiary learners to read electronically in cases where texts were “short…[and] of less importance, relevance, and difficulty” (Mizrachi and Salaz, 2020, p. 817).…”
Section: Ream Modelmentioning
confidence: 98%
“…Based on the available evidence, we further endorse the argument of Ross et al (2017) that print vs digital format dichotomies can oversimplify this complex phenomena, and with our model we attempt to answer the question posed by Mizrachi and Salaz – not whether, but under what conditions – “WHEN do they [readers] prefer print and WHEN electronic?” (2020, p. 816).…”
Section: Ream Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Even during the pandemic, “Print books continued to dominate the market during the year,” ( Anderson, 2021 ). To the surprise of many in various areas of education, studies continued to show that tertiary students preferred to read their academic texts in print for deep learning tasks such as when they needed to focus and internalize the information ( Dilevko & Gottlieb, 2002 ; Liu, 2006 ; Mizrachi, 2015 ; Mizrachi & Salaz, 2020 ). One of the largest studies to date documenting this phenomenon is the Academic Reading Format International Study (ARFIS) ( Mizrachi et al, 2021 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Final quantitative analysis of all 21,265 students in 33 countries ( Mizrachi et al, 2021 ) confirmed earlier findings. ARFIS researchers then performed a qualitative analysis of English language comments by students categorized as either print preferrers or electronic preferrers to discover the reasons for their preferences, and under what circumstances they would consider reading a text in their less preferred format ( Mizrachi & Salaz, 2020 ). Results showed that while students may have had a preferred format, their behaviors were flexible and depended on circumstances surrounding the reading task such as its importance to their coursework, the length of the reading and convenience of access.…”
Section: Literature Reviewmentioning
confidence: 99%